Elicit, Explain, Evaluate: Module Writing Model - Manoos, Liza Marie (International Journal of Arts, Sciences and Education, 2022)
Rethinking of new teaching pedagogies effected by the new set-up in education both globally and locally was a force result of the 2019 pandemic. Face-to-face mode of learning has been challenging in the Philippines since March of school ear 2019-2020 thus every educator was obliged to find means on how to deliver instruction in the most practical and effective ways. Pedagogies in delivering instruction shifted to a blend using pinted modules sent to the learners, online classes and the like. In order to the adhere to the Commission on Higher Education order that academic instruction be delivered in flexible manner so long as learners are reached out. In August, the beginning of school year 2020-2021 Marinduque State College (MSC) gave the teachers leeway to use any mode of teaching. Thus, the faculty members used instructional materials readily available. As a fact brought about by the sudden shift in teaching mode 82% of the research respondents was using teaching-learning materials. As an ISO certified institution the author devised a model deemed useful in writing modules as instructional material. The comprehensive model comprised the basic steps in presenting a lesson. Its parts are Elicit, Explain and Evaluate (3Es). The 3Es model is a module wriing guide that introduces three major sections for instructional material. The Elicit provides the objectives of the learning material, review of previous knowledge and optional pre-assessment activities. The Explain section discusses the content of the material. Illustrations and non-linguistic representations are presented in this section. The Evaluate section provides the assessment and learning reinforcement activities for the learners. The model has been developed to provide a concise and clear guideline in developing instructional materials to be usd for blended learning schemes and as an identity of MSC. This model has been recommended by Marinduque State College's Academic Affairs Department which has been used in standardizing instructional materials things required for accreditation and quality assurance.